Análise de uma sequência de ensino investigativo no Parque Estadual Pedra Azul-ES - Cesconetto, Daiane Barbosa (2024)
The general objective of this research was to analyze the development of an Investigative Teaching Sequence (SEI), applied in Pedra Azul State Park, ES, adopting the principles and stages of Science Teaching through Inquiry, together with a group of 8th grade students from a state school in Conceição do Castelo, ES. The theoretical framework is based on the historical-cultural perspective, using a qualitative approach of collaborative intervention research. Data production occurred from the elaboration and application of an Investigative Teaching Sequence (SEI), according to the stages proposed by Carvalho (2013): problematization and hypothesis raising, hypothesis testing, systematization and contextualization of knowledge. We used the theory of mediated action to describe the stages of the SEI, considering the five elements that compose it (scene, agents, purpose, cultural tools and act), as pointed out by Wertsch (1999). The techniques and procedures used to analyze the data were records in the students' logbooks, photographs, audio recordings to capture the students' spoken discourse, and an investigative script that guided the SEI stages. The results showed that pedagogical mediation, combined with the use of non-formal spaces and the approach of Science Teaching through Inquiry, contributed significantly to student learning, achieving good results in the construction of scientific knowledge. The activities developed aroused great engagement, promoting protagonism and the active construction of knowledge. In addition, they favored the development of essential skills, such as observation, critical analysis, hypothesis formulation, and problem solving. At the end of the research, a Teaching Guide was prepared with the objective of guiding, inspiring, and encouraging other elementary school teachers to carry out this type of activity.